Thromboprophylaxis an update of current practice: Can we reach a consensus?. Issue 4 (December 2019) - Ricci, William M.; Broekhuyse, Henry; Keating, John F.; Teague, David C.; White, Timothy O.
Abstract : Abstract: Diagnosis, prophylaxis, and management of venous thromboembolism (VTE) in patients with fractures remain a highly controversial topic with little consensus in clinical practice or the literature. The following manuscript represents a summary of evidence presented at the 2017 OTA Annual Meeting Symposium; "Thromboprophylaxis an Update of Current Practice: Can We Reach A Consensus?" The need for prophylaxis in pelvic and acetabular fracture patients; the existing body of evidence related to VTE, pulmonary embolism (PE), and prophylaxis for patients with fractures about the knee; current evidence in Edinburgh Scotland, regarding VTE prophylaxis in patients with isolated ankle fractures and the risk of VTE in patients with a hip fracture are topics that are addressed. The reader will benefit from the wisdom of this compilation of global contributions on thromboprophylaxis.